Identification of a Large DNAJB2 Deletion in a Family with Spinal Muscular Atrophy and Parkinsonism. Issue 11 (21st August 2016) - Sanchez, Elena; Darvish, Hossein; Mesias, Roxana; Taghavi, Shaghyegh; Firouzabadi, Saghar Ghasemi; Walker, Ruth H.; Tafakhori, Abbas; Paisán‐Ruiz, Coro
Abstract : (A) Pedigree of a family with Spinal Muscular Atrophy and Parkinsonism due to (B) a large DNAJB2 (HSJ1b) deletion. (C) HSJ1b protein (left) and mRNA (right) levels were significantly decreased in mutant transfected cells. (D) Cells transfected with mutant HSJ1b showed more apoptotic nuclei and aggregates (white arrows) (E) as well as higher levels of LC3 expression (yellow arrows). (F) Zoomed images of a wild‐type cell with low levels of LC3 (left) and a mutant cell with high levels of LC3 (right). ABSTRACT: In this study, we described the identification of a large DNAJB2 (HSJ1) deletion in a family with recessive spinal muscular atrophy and Parkinsonism. After performing homozygosity mapping and whole genome sequencing, we identified a 3.8 kb deletion, spanning the entire DnaJ domain of the HSJ1 protein, as the disease‐segregating mutation. By performing functional assays, we showed that HSJ1b‐related DnaJ domain deletion leads to loss of HSJ1b mRNA and protein levels, increased HSJ1a mRNA and protein expressions, increased cell death, protein aggregation, and enhanced autophagy. Given the role of HSJ1 proteins in the degradation of misfolded proteins, we speculated that enhanced autophagy might be promoted by the elevated HSJ1a expression seen in HSJ1b‐deficient cells. We also observed a significant reduction in both tau and brain‐derived neurotrophic factor levels, which may explain the dopaminergic deficits seen in one of the affected siblings. We concluded that HSJ1b deficiency leads to a complex neurological phenotype, possibly due to the accumulation of misfolded proteins, caused by the lack of the DnaJ domain activity. We thus expand the phenotypic and genotypic spectrums associated with DNAJB2 disease and suggest relevant disease‐associated mechanisms.